Effect of Photoperiod and Ascorbic Acid Concentration on Degree of Browning, Shoot Regeneration and Survival of Plantain (Musa ssp.) Cultivars Growing in vitro - Levai, Lewis D.; Ngone, Mercy A.; Monono, Ekwa Y.; Ngale, Jemimah E.; Nsimi, Armand; Yaya, Forkwa Victorine; Oumar, Doungous; Achidi, Eric; Bechem, Eneke T. (European Journal of Applied Sciences, 2023)
Plantain, an important crop in Sub-Saharan Africa, faces challenges such as low fertility and susceptibility to stresses. Micropropagation techniques offer disease-free planting materials, but success depends on various factors. This study explored the effects of ascorbic acid (AA) concentration and photoperiod on browning, shoot regeneration, and survival of explants in in vitro culture. Three plantain cultivars and four AA concentrations were examined, with explants subjected to darkness and a light/dark cycle. Browning, shoots/buds per explant, shoot height, and survival were measured. Results showed that darkness reduced browning compared to light, particularly in the French Clair and Batard cultivars. Preservation of AA in darkness prevented browning by inhibiting its decay and reducing enzyme activity related to phenolic compounds. Photoperiod did not significantly affect shoot characteristics or survival, while AA concentration had a significant impact on shoot regeneration. The Batard cultivar exhibited highest regeneration with 50mg/L AA, while higher concentrations had a negative effect. Therefore, incubating explants in darkness effectively reduces browning during in vitro culture. Optimal AA concentration (50mg/L) enhances shoot regeneration, while higher concentrations should be avoided. These findings have implications for improving micropropagation techniques, addressing plantain production challenges, and meeting the demand for high-quality planting materials in Sub-Saharan Africa.